THE INFLUENCE OF GENDER ON THE STUDENTS’ LEARNING OUTCOMES IN SOCIAL SCIENCE SUBJECT AT GRADE V SDN 2 SIDOREKSO KUDUS - Lisa Nurulita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to determine the effect of gender on the students’ learning outcomes in social science subject at grade V SDN 2 Sidorekso Kudus. This study was quantitative research using a comparative research design with descriptive statistical research methods. The population in this study consisted of 36 students at the fifth grade of SDN 2 Sidorekso Kudus, with 18 male students and 18 female students. The samples were all grade V students who were selected by using nonprobability sampling technique with saturated sampling. The data used in this study were secondary data or existing data, namely the scores of social science subject taken from the students’ report cards. The data were analyzed by using one-sided t-test (right side). Based on the analysis results, it was found that tcount > ttable (2.549 > 2.032). Thus, it was indicated that gender affected the students' learning outcomes, especially for social science subject. The average score for male students was 81.389, and the average score for female students was 83.667.